Analysis of Genetic Variations of Ceiba pentandra (L.) Gaertn. on Several Critical Lands in West Sumatra Using RAPD Molecular Markers (Biosaintifika: Journal of Biology & Biology Education, 2023)
Ceiba pentandra (L.) Gaertn. is a plant whose fruit is used to produce fiber and seeds for biofuel, which has the potential to be developed in critical land because it is adaptive to grow in critical land that is less fertile and lacks water. In West Sumatra, several critical land locations are overgrown by C. pentandra plants. This study aims to determine the genetic variation of C. pentandra in five critical land populations in West Sumatra as the basis for selecting superior seeds for development in critical land. The research was conducted by the descriptive method using molecular data with the molecular marker RAPD (random amplified polymorphic DNA). The results showed that the primers OPA-01, OPA-02, and OPB-10 could detect polymorphisms. Pangkalan Koto Baru in the regency Lima Puluh Kota (H = 0.1212) was the population with the highest intrapopulation genetic variation value. Interpopulation genetic variation (DST = 0.0321) was lower than intrapopulation genetic variation (HS = 0.1021), with a low genetic differentiation value (GST = 0.2392) and a high gene flow value (Nm = 1.5894). The genetic variation of C. pentandra can be used to select the parent in plant breeding programs.